2013
DOI: 10.1007/s00345-013-1132-1
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in bladder control: from babies to elderly

Abstract: In both sexes, there are anatomical and behavioral differences in dealing with bladder control, as well as voiding and incontinence. Despite intensive research within the last decades, the differences in physiology and pathophysiology as well as gender differences of bladder control and continence are still poorly understood and further research is highly needed. In babies, gender difference seems to be most likely caused by a difference in maturity rate of the bladder. After gaining bladder control, behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…In a study by Petrangeli et al, where young women with LUTS in childhood were reevaluated in adulthood, the prevalence of nocturia was 37% in those with a history of NE (19 patients) and 46% in those with a history of daytime LUTS, findings that are in line with our results based on patients with NE with or without daytime LUTS. 7,8 This finding is in line with the clinical observation that for 2 or more nocturnal voids the prevalence was 9.2% in girls and 2.4% in boys. 7,8 This finding is in line with the clinical observation that for 2 or more nocturnal voids the prevalence was 9.2% in girls and 2.4% in boys.…”
Section: Department Of General Practice University Medical Center Grosupporting
confidence: 89%
“…In a study by Petrangeli et al, where young women with LUTS in childhood were reevaluated in adulthood, the prevalence of nocturia was 37% in those with a history of NE (19 patients) and 46% in those with a history of daytime LUTS, findings that are in line with our results based on patients with NE with or without daytime LUTS. 7,8 This finding is in line with the clinical observation that for 2 or more nocturnal voids the prevalence was 9.2% in girls and 2.4% in boys. 7,8 This finding is in line with the clinical observation that for 2 or more nocturnal voids the prevalence was 9.2% in girls and 2.4% in boys.…”
Section: Department Of General Practice University Medical Center Grosupporting
confidence: 89%
“…They also found that lower urinary tract symptoms in both sexes start to develop from the fourth decades. "Men and women handle the problem variedly showing gender differences in coping strategies with better coping mechanisms in women" [13]. In our study, our patients showed diversity in symptoms distribution.…”
Section: Discussionmentioning
confidence: 52%
“…Our results are consistent with Bauer and Huebner, who found women to be more experienced with coping strategies in handling their LUTS and using pads to prevent urine leakage. Men are not used to buying and wearing pads [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seitz and Fajkovic [11] identify gender-specific aspects in the prevalence, treatment and aftercare in urolithiasis patients with special attention to gender aspects associated with a history of kidney stones. Bauer and Hübner [12] provide a deeper insight into gender differences of bladder control and dysfunction. In the article on bladder outlet obstruction in men, Klatte et al [13] identify clinical predictors with first episode of spontaneous acute urinary retention in order to facilitate patient selection for early deobstructive prostate surgery.…”
mentioning
confidence: 99%